Pengaruh Mekanisme Good Corporate Governance Dan Struktur Kepemilikan Terhadap Pengungkapan Sustainability Report - Masiyah Kholmi; Muhammad Nizzam Zein Susadi (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Muhammadiyah Riau, 2021)
This research has a purpose to analysis the effect of good corporate governance mechanism and ownership structures on the disclosure of sustainability reports. Purposive sampling method was applied sampling technique certain of criteria. The sample is 47 companies from a population of 627 companies listed on the Indonesia Stock Exchange (BEI) in 2018. Data collection techniques used the documentation method. This research uses data analysis tools with the Smart PLS 3 application to test hypotheses. The results showed that the variables of good corporate governance mechanisms that were proxied by the audit committee, the independent board of commissioners, and the board of directors had a significant effect on the disclosure of sustainability reports, ownership structure variables that were proxied with managerial ownership, institutional ownership, and foreign ownership also affected the disclosure of sustainability reports